Comparison Of Carbon Oxidation Losses From A Bare Drained Peatland Using Different Techniques - Mos, Hasimah (2023)
Drainage and cultivation of peatlands will lead to subsidence and mineralization of organic matter that increases C loss as more CO2 is emitted. Measurement of CO2 emissions were made at a newly logged-over peat swamp area that has been cleared of vegetation. Three different methods were used; eddy covariance, soil chamber and soil subsidence measurements to derive CO2 emissions in this study. The average above ground CO2 flux rate measured by the eddy covariance technique was 5.13±0.12 μmol CO2 m-2 s-1 (or 71.18 tonnes CO2 ha-1 year-1). The soil CO2 efflux rate measured by the soil chamber technique was 3.88±0.15 μmol CO2 m-2 s-1 (or 53.84 tonnes CO2 ha-1 year-1). Subsidence amounted to 1.21±0.13 cm year-1 over the measured year, which corresponds to 24.60 tonnes CO2 ha-1 year-1. Differences in estimated C losses might not depend exclusively on the method of measurement, but also on the area and period of measurements. This could be attributed to the spatial and temporal variability, measuring techniques, environmental conditions, and heterogeneity of peat properties. In this study, the soil chamber method was found to be a reliable and cost-effective approach for assessing carbon loss compared to eddy covariance and subsidence techniques. The study provides valuable information on carbon emission baseline from peat due to drainage-induced oxidation that excludes the plant root respiration component. The data will be helpful in making decisions about Malaysia's future peatland agricultural development.